Negative refraction in hyperbolic metamaterials - Qin, Yuejing (2019)
The project discusses the means of achieving negative refraction through the implementation of multiple-layered hyperbolic architecture with InSb and Al2O3 (InSb-Al2O3). An initial literature review outlined that such metamaterials can reduce loss, simplify fabrication and broaden effective bandwidth compare with the materials that are already known. Upon the calculation of frequency region in MATLAB, subsequent COMSOL simulations confirmed that negative refraction could be realized in the Terahertz (THz) frequency range for the HMM structure. The project work concluded with two aspects: the realization of negative refraction in the simulation of COMSOL and the electric field on the surface of metamaterials which show the capability of their super-resolution. These simulation results may lead to advanced optical devices such as superlens in Terahertz frequencies with low loss and simple fabrications.